Endovascular entry closure using Amplatzer vascular plug for the aortic dissection in sub-acute phase - Hata, Yosuke (J Cardiol Cases, 2017)
Enlargement due to residual dissection after surgical ascending aortic replacement is technically challenging to treat. Endovascular entry closure using an Amplatzer vascular plug 2 (AVP2) in the sub-acute phase has not been reported. A 75-year-old female underwent emergent ascending aorta replacement for Stanford type A aortic dissection. Postoperative computed tomography angiography (CTA) showed a distal aortic arch diameter of 41 mm and a patent false lumen. CTA one month after the operation revealed distal aortic arch enlargement to 52 mm, which is considered high-risk for rupture. Repeat open surgery was considered but carried a high risk of perioperative complications. Therefore, we performed endovascular closure for the entry at the proximal descending aorta using an AVP2 and stent graft coverage and coil embolization for the re-entries at the bilateral iliac arteries. CTA one month after the procedure revealed that the false lumen of the aortic arch was thrombosed and that the distal aortic arch had shrunk to 38 mm, indicating the efficacy of endovascular entry closure with the AVP2 after aortic dissection. <Learning objective: Endovascular entry closure for residual dissection more than 2 years after ascending aorta replacement has already been reported. We conducted this procedure in the sub-acute phase and induced favorable aortic remodeling. The endovascular entry closure was successfully conducted for a patient presenting residual tears after emergent ascending aorta replacement, considering a treatment option with high risk for repeat open surgery.>